The character of the Just City: the regulation of place distinctiveness and its unjust social effects. Issue 3 (May 2017) - Davison, Gethin
Abstract : The concept of 'character' has gained considerable currency in city planning and design, with the impacts of proposed property developments on the character of established urban places now a common consideration in planning decision making. Drawing on the methods of critical discourse analysis, this paper problematises this trend through a case study of Melbourne, Australia. Three critiques of current approaches to the regulation of character in Melbourne are identified: an overemphasis on physical form and disregard for the perceptual and experiential dimensions of place, a failure to acknowledge insider perspectives on character, and the effects of character-based regulations in justifying inequitable and exclusionary planning outcomes. The difficulties associated with the use of character as a planning assessment criterion are then discussed. The paper concludes by arguing for approaches to the regulation of place distinctiveness that attend more fully to the social and experiential aspects of place.